La ficción transcultural entendida como literatura traducida en el polisistema poscolonial - Sales Salvador, Dora (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
For a great number of fictional writers in the postcolonial paradigm pluralism is organic, translation is an inevitable way of life, and translation consciousness and strategies can be a way of reinforcing rather than weakening different linguistic and cultural identities, because above all translation is used as a way to get access to the central arena of the postcolonial polysystem: it is a powerful tactic within a larger movement of cultural resistance. This paper intends to reflect upon how the study of these transcultural fictions understood as translated literature within the global polysystem, may be of great help when it comes to delineating a theoretical reflection on post- colonial translation practice. Such study should provide us with a better understanding of: a) the form and function of these literatures, and b) possible strategies for the translation of culturally heterogeneous texts, in the light of what authors who translate themselves have done. The specific literary examples we will mention to illustrate our points are the transcultural narratives of the Peruvian José María Arguedas and the Indian Vikram Chandra.